Changes in T lymphocyte subsets in peripheral blood of patients with middle-advanced cervical cancer before and after nimotuzumab combined with concurrent chemoradiotherapy - Man Ao; Pengyu Li; Dongxue Sun; Xiaojun Li; Shulei Xu; Yuntao Hao (Taylor & Francis Group, 2023)
The current study sought to investigate the effect of nimotuzumab combined with concurrent chemoradiotherapy (CCRT + Nim) on T lymphocyte subsets in middle-advanced CC. Firstly, patients with middle-advanced CC were administered CCRT or CCRT + Nim. Next, levels of T lymphocytes in peripheral blood of CC patients pre- or post-treatment and healthy females were determined by flow cytometry. The short-term efficacy was evaluated, and overall survival (OS) and progression-free survival (PFS) of patients were recorded. In addition, the correlation of T lymphocyte subsets post-treatment with OS/PFS was assessed with Pearson analysis. CC patients exhibited decreased total T cells/T helper cells/CD4+/CD8+ ratio and increased T suppressor cells/Tregs in peripheral blood. Meanwhile, CCRT and CCRT + Nim improved T lymphocyte subset imbalance, with CCRT + Nim exhibiting better efficacy. CCRT + Nim exhibited better short-term efficacy and higher PFS than CCRT, with no evident difference in OS. The levels of total T cells/T helper cells/T suppressor cells/Tregs were not significantly-correlated with OS/PFS, and the CD4+/CD8+ ratio was correlated with PFS but not OS. Collectively, CCRT + nimotuzumab ameliorate the imbalance of T lymphocyte subsets in peripheral blood of middle-advanced CC patients, and the CD4+/CD8+ ratio after therapy is correlated with PFS.IMPACT STATEMENT What is already known on this subject? The utilisation of Nimotuzumab targeting epidermal growth factor receptor (EGFR) combined with concurrent chemoradiotherapy (CCRT) as an efficient treatment for middle-advanced cervical cancer (CC) has garnered the attention of numerous researchers over the years. T cells represent a major immune cell type in the tumour microenvironment and serve as the basis for maintaining cellular immune functions. What do the results of this study add? Our findings revealed that nimotuzumab combined with CCRT improves the abnormality of T lymphocyte subsets in peripheral blood of patients with middle-advanced CC, such that the CD4+/CD8+ ratio after treatment was significantly correlated with progression-free survival (PFS). What are the implications of these findings for clinical practice and/or further research? CCRT of CC may have a short-term negative impact on the peripheral T-cell immune micro-environment, and the combination of nimotuzumab, cisplatin-based chemotherapy, and radiotherapy enhances the frequency of Tregs in peripheral blood. Our findings illustrated that nimotuzumab combined with CCRT can improve the imbalance of T lymphocyte subsets in peripheral blood of patients with middle-advanced CC. A better understanding of the mechanisms of these therapies will optimise the selection of patients most likely to benefit from treatment, serving as a reference for further research on the relationship between EGFR-specific T cells and clinical benefit in patients treated with nimotuzumab in combination with CCRT.